Architecture for Personalized Meta Search Engine - Borkar, NA; Kulkarni, SV (International Journal of Computer Sciences and Engineering, 2025)
Information available on the web is growing rapidly. A major problem in web search is that the interactions between the users and search engines are limited by the factors like unknown capabilities of search engines adopted, and ill-constructed query by the user. Hence the user has to repeatedly apply the several queries till he reaches the pages of most interest. Any search engine can give its best performance if well-constructed and detailed queries are used. As a result, the users tend to submit shorter/ insufficient/ ambiguous queries yielding unwanted search lists. In order to return highly relevant results to the users, search engines must be able to profile the users’ interests and personalize the search results according to the users’ profiles. This paper discusses the need and specific requirements of personalized search engine, its architecture, the prototype model developed and the results obtained. Also sample sessions performed on the designed model have been given for selected user profile.